Exploration of PROMETHEE II and VIKOR methodology in a MCDM approach for ascertaining the optimal performance-emission trade-off vantage in a hydrogen-biohol dual fuel endeavour. (15th December 2017) - Debbarma, Bishop; Chakraborti, Prasun; Bose, Probir Kumar; Deb, Madhujit; Banerjee, Rahul
Abstract: In order to meet the challenges of global energy insecurity and the increasing obligation of complying with the environmental legislation, a paradigm shift from the reliance of conventional fossil fuel resources in IC engine domains are being increasingly witnessed. Exhaustive research has been carried out with non-conventional and alternative fuels resources in the off-road and transportation sector to meet the challenges of exploring a potential alternative to conventional diesel fuel with the additional objective of meeting the ever increasing stridency of the emission mandates. Among various alternative fuels, hydrogen whose clean and green burning characteristics has proven to be viable, sustainable fuels in IC engine domains with the premium quoting as one of the significant low emission signature than conventional fuels. Biodiesel, on the other hand, presents itself as a ready-to-use sustainable alternative in diesel powertrains in the environment of its National agricultural and rural economic development potential. As hydrogen is deemed to increase NOx emission when it is used with biodiesel, ethanol (20% v/v) blend with biodiesel has been used as a viable NOx suppression measure owing to its superior miscibility in methyl ester in comparison to conventional diesel. To this end, single cylinder diesel engine has been made to operate in a dual fuel mode with hydrogen as the dual fuel and mahua methyl ester with ethanol in blend as pilot fuel. The present aims of the study are to choose the best suitable fuel combination among the alternatives, in relation to various attributes chosen especially with an eye to address the performance-emission trade-off potential of the dual fuel operation. The most appropriate duel fuel combination out of ten alternatives has been discerned through distinct multi-criteria decision making (MCDM) methodologies. Analytic Hierarchy Process (AHP) has been applied for finding the weightage of each criterion and ranks of the alternatives investigated have been calculated by using VIKOR and PROMETHEE II methods. The alternative which signified biodiesel under hydrogen enrichment, at hydrogen injection duration of 9000 µs at a constant engine speed of 1500 RPM, was discerned as the the most appropriate alternative fuel combination at 75% load since it has been ranked first by both the MCDM methods. At full load for PROMETHEE II it was alternative A4, and for VIKOR it was observed as alternative A3 which signified biodiesel under hydrogen enrichment at hydrogen injection duration of 7000 µs at 1500 RPM. Alternatively, A10 strategy which indicate biodiesel ethanol blend along with hydrogen enrichment at hydrogen injection duration of 13, 000 µs at 1500 RPM was observed to be the least preferential amongst the alternative for both the MCDM methods, at both 75% and 100% loads. Since there was consistency in the ranking, in order to judge the performance of both the methods Spearman's Rank Correlation Coefficient was calculated and was observed to be within acceptable levels lending an index of robustness of the optimal choices of the strategies advocated by the MCDM methodologies adopted in the present case study.